Our cosmic neighborhood: the Solar System - Lazzaro, Daniela (Cadernos de Astronomia, 2024)
The Solar System and its countless and distinct bodies compose the neighborhood of our home, the Earth. In this text beside performing a general inventory of the objects presently known we also highlight the similarities and differences among them and what this tells us regarding their formation and/or evolution. Although the Solar System bodies are the best that we know of all the immense universe around us, even though many questions are still lacking a satisfactory answer and appear as challenges for the future.